Application of parallel ensemble Monte Carlo technique in charge dynamics simulation - A. P. Othman,; R. Umar,; G. Gopir, (Universiti Kebangsaan Malaysia, 2008)
In the past, simulating charge dynamics in solid state devices, such as current mobility, transient current drift velocities are done on mainframe systems or on high performance computing facilities. This is due to the fact that, such simulations are costly in terms of computational requirements when implemented on a single processor-based personal computers (PCs). When simulating charge dynamics, large ensembles of particles are usually preferred, such as exceeding 40000 particles, to ensure a numerically sound result. When implementing this type of simulation on a single processor PCs using the conventional ensemble or single particle Monte Carlo method, the computational time is very long even on the fast 2.0 MHz PCs. Lately, a more efficient, easily made available tools and cost effective solution to this problem is the application of an array of PCs employed in a parallel application. This is done using a computer cluster network in a master-slave model. In this paper we report the development of a LINUX cluster for the purpose of implementing parallel ensemble Monte Carlo modelling for solid states device. We have proposed the use of Parallel Virtual Machine (PVM) standards when running the parallel algorithm of the ensemble MC simulation. Some results of the development are also presented in this paper.